(untitled) (Lafia Journal of Scientific and Industrial Research, 2025)
This paper examines the fatty-acid profiles, physicochemical properties, functional lipid indices and phytosterol composition of oils in the kernels and pulps of three underexploited fruits namely; Hyphaene thebaica (Doum palm), Diospyros mespiliformis (Jackal-berry), and Detarium senegalense (Sweet detar) as found in North-East Nigeria. The standard analytical techniques were used for different analyses. Physicochemical measurements indicated obvious species- and tissue-specific differences, Doum palm kernel having the highest acid and viscosity, and peroxide levels were low in all samples, meaning there were minimal oxidative damages. The oils were anaesthetized by colour parameters (CIELAB) as being light, with mild rates of the green-yellow liquids and sample-specific brightness. The fatty-acid analysis showed the highest level of myristic acid (8.27 %) in jackal-berry kernel and the highest content of oleic acid (30.20 %) in sweet detar pulp. Linoleic and α-linolenic acids were present in physiologically relevant amounts, the highest values recorded in jackal–berry pulp (28.50 %) and jackal–berry kernel (16.83 %), respectively. The quality of lipid indices showed positive nutritional profiles with MUFA/SFA and PUFA/SFA ratios being over 1.00 with low atherogenicity and thrombogenicity indices and ω-6/ω-3 ratios in the anti-inflammatory range values. Phytostersol analysis revealed that sweet detar pulp has the highest sitosterol (0.823 mg/100 g) and ergosterol (0.653 mg/100 g); doum kernels showed high level of campesterol (0.747 mg/100 g) and avenasterol (0.83 mg/100 g). Generally, these results highlighted the nutritional value, biochemical composition, and functional prospects of these underexploited fruit oils, thereby recommending them as foods, nutraceutical and cosmetic ingredients.